2009
DOI: 10.1111/j.1440-1746.2009.05858.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic risk factors associated with erosive esophagitis

Abstract: Obesity and hypertriglyceridemia, which are key components of metabolic syndrome, are moderate independent risk factors for erosive esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Regarding the individual components of metabolic syndrome, hypertension suggested by SBP was the most important mediator of both overweight-ERD and obesity-ERD association. Our findings regarding cardiometabolic risk factors are supported by previous studies on metabolic syndrome components and ERD 3537 . They reported a significant relationship between ERD and metabolic parameters, such as dyslipidemia (especially hypertriglyceridemia), hyperglycemia, and hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the individual components of metabolic syndrome, hypertension suggested by SBP was the most important mediator of both overweight-ERD and obesity-ERD association. Our findings regarding cardiometabolic risk factors are supported by previous studies on metabolic syndrome components and ERD 3537 . They reported a significant relationship between ERD and metabolic parameters, such as dyslipidemia (especially hypertriglyceridemia), hyperglycemia, and hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…Of these, 19 studies (18 independent populations) reported the association between central adiposity and EE, 12,14,2743 17 studies (15 independent populations) reported the association between central adiposity and BE, 911,13,16,35,4454 and 6 studies reported the association between central adiposity and EAC. 13,5559 Lee et al 33,34 reported the relationship between central adiposity and EE by using both WHR and CT-measured visceral adipose tissue area (in a subset of patients).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 40 studies, 18 were performed in the Asian population (including 17 studies on risk of EE) 12,14,2734,3743 and the remainder in the Western population. Eight studies used visceral adipose tissue area as measure of central adiposity (4 each in patients with EE 12,28,29,34 and BE 16,44,46,53 ), 23 studies used WHR (7 studies on EE, 30,3437,39,40 11 studies on BE, 911,13,35,4852,54 and 5 studies on EAC 13,5659 ).…”
Section: Resultsmentioning
confidence: 99%
“…Male gender, hiatal hernia, Helicobacter pylori infection, smoking, and alcohol consumption can increase the risk of erosive esophagitis (EE) [3, 4]. In addition, common features of metabolic syndrome are risk factors for EE [5, 6]. …”
Section: Introductionmentioning
confidence: 99%